Effect of Privacy and Safety, Communication, and Physical Environment on Patient Satisfaction and Their Impact on Loyalty (Study at a Dental Clinic in West Jakarta) - Annamaria Gabriela; Pauline H.P. Tan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
To determine the effect of privacy and safety, communication, as well as physical environment mediated by patient satisfaction on patient loyalty (Study at a Dental Clinic in West Jakarta). Method: The type of research used is quantitative using the PLS-Structural Equation Modeling (SEM) approach using SMART PLS software. The sample used in this study were 290 dental clinic consumers. Data collection tools in the form of a questionnaire. Result: Privacy and safety, communication, and physical environment have a positive and significant impact on patient satisfaction. Patient satisfaction has a significant and positive effect on customer loyalty. Conclusion: Privacy and safety, communication, and physical environment mediated by patient satisfaction on patient loyalty are all supported hypotheses.